2017
DOI: 10.1186/s13104-017-2967-0
|View full text |Cite
|
Sign up to set email alerts
|

Serotyping and antibiotic susceptibility patterns of Vibrio and Shigella isolates from diarrheal patients visiting a Tropical and Infectious Diseases Hospital in central Nepal

Abstract: BackgroundDiarrheal diseases are the major infectious disease in developing countries like Nepal. Lack of proper sanitation and antimicrobial resistance gained by microbes have challenged to address diarrheal diseases in resource-limited countries. Early diagnosis of disease and proper antibiotic treatment can significantly reduce the disease burden. This study was designed to determine the recent antimicrobial susceptibility pattern of Vibrio cholerae and Shigella spp. to assure the proper antibiotic treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
(15 reference statements)
0
2
0
Order By: Relevance
“…This result is congruent to the studies performed by Dhital et al (2017), where 93% of Shigella isolates were susceptible to Ceftriaxone, and by Kansakar et al (2006), where 100% of Shigella isolates were susceptible. In similar settings, Maharjan et al (2017) found 97% of Shigella species, and Thapa et al (2017) found 71.4% of Shigella species susceptible to Ceftriaxone. Several studies across the world have also shown the increased resistance of Shigella species to third-generation cephalosporins (Radice et al, 2001;Vinh et al, 2009;Mandal et al, 2010).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…This result is congruent to the studies performed by Dhital et al (2017), where 93% of Shigella isolates were susceptible to Ceftriaxone, and by Kansakar et al (2006), where 100% of Shigella isolates were susceptible. In similar settings, Maharjan et al (2017) found 97% of Shigella species, and Thapa et al (2017) found 71.4% of Shigella species susceptible to Ceftriaxone. Several studies across the world have also shown the increased resistance of Shigella species to third-generation cephalosporins (Radice et al, 2001;Vinh et al, 2009;Mandal et al, 2010).…”
Section: Discussionmentioning
confidence: 86%
“…In the studies in Nepal from 1995 to 2002, the prevalence of S. dysenteriae was higher than the S. flexneri, while in the studies done from 2003 to 2005, S. flexneri was found to be the predominant species (Kansakar et al, 2006). The recent studies conducted in India (Puzari et al, 2018), Nepal (Maharjan et al, 2017;Thapa et al, 2017), Iran (Nikfar et al, 2017), China (Chang et al, 2016), and Latin America (Sati et al, 2019) show that S. flexneri is the predominant species. On the other hand, nations such as England (Bardsley et al, 2020), Australia (O'Sullivan et al, 2002Ingle et al, 2020), and the United States (Kozyreva et al, 2016) showed a higher predominance of S. sonnei.…”
Section: Discussionmentioning
confidence: 99%